Narrative review on the development and challenges of PIPA education in China - Long, Siyu; Ang, Mei Foong; Mohd Norowi, Noris (Malque Publishing, 2025)
As a traditional Chinese folk instrument with a history of 2,000 years, the pipa has been valued by the Chinese government and favored by the Chinese people for its unique sound and rich expressive power. However, the development lineage and current status of pipa education in China have rarely been clarified, especially the current status of pipa education. This study used narrative review techniques to organize and analyze the history and current status of pipa education. This paper reviews the history of pipa education in China, focusing on the current development of pipa education, including teaching institutions, representative figures, target students, and teaching models. The study revealed that contemporary Chinese pipa education has achieved remarkable accomplishments. China’s eleven conservatories serve as the primary institutions for imparting contemporary pipa education. Representative figures such as Lin Shicheng, Wang Fangdi, and Liu Dehai have made substantial contributions to the advancement of contemporary pipa education. However, pipa instruction is primarily targeted toward children and university students, with limited emphasis on elderly people and special children. Individual and group lessons in traditional pipa instruction possess their respective merits and drawbacks. Nonetheless, further exploration is warranted regarding integrated teaching models and the application of contemporary information technology in innovative teaching models to facilitate the advancement of modern pipa education.